Time Delay Estimation in the Presence or Correlated Noise and Reverberation - Rui, Yong; Florencio, Dinei (Microsoft Research, 2003)
We propose a new two-stage framework for time delay estimation in the presence of correlated noise and reverberation. The new framework allows us to develop a set of new approaches as well as to unify existing ones. We further develop the maximum likelihood estimation when reverberation is present. The corresponding weighting function is a more accurate form of the weighting function proposed in [10], one of the best existing techniques. We compare our new algorithms with the existing ones and report superior performance.